Analysis of the Learning Process for Multiplication and Division Using Flashcard Media Among Third-Grade Elementary School Students - Heru Dwi Wahyuni; Riyadi Riyadi; Septi Triyani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
This study addresses the gap between curriculum expectations and classroom practices in learning multiplication and division in elementary school, where students often rely on memorization rather than conceptual understanding. The purpose of this study is to analyze the learning process using flashcard media in facilitating Grade 3 students’ conceptual understanding. This study employed a qualitative descriptive approach conducted in a third-grade classroom with 28 students. Data were collected through classroom observations and semi-structured interviews, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that flashcards support conceptual understanding by encouraging students to use strategies such as repeated addition and equal sharing. Teacher scaffolding and repeated exposure help students correct errors and build connections between operations. The study concludes that flashcards are effective when integrated with structured instruction and guided questioning to support meaningful learning.